The influence of chronic stress imposed on pregnant rats on the induced bone loss in their adult offspring - Semenoff-Segundo, Alex; Delle Vedove Semenoff, Tereza Aparecida; Borges, Alvaro Henrique; Miranda Pedro, Fabio Luiz; Caporossi, Leonardo Stephan; Bosco, Álvaro Francisco [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Background and objective: Stress during pregnancy may alter offspring susceptibility to diseases during adulthood. In the present study, female Lewis rats were subjected to chronic stress during the gestational period, and the effect of this stress was evaluated histometrically on the progression of ligature-induced bone loss in their adult offspring.Material and methods: After confirming pregnancy, half of the pregnant rats were randomly designated as control animals (no stress regimen was imposed), and the other half was submitted to a chronic stress model (immobilization at cold temperature) between the 7th and the 18th gestational day. After birth, 12 male rats delivered by stressed mothers - Group 1 (G1) - and 12 male rats delivered by non-stressed mothers - Group 2 (G2) - were selected. When birthed rats reached 250 g of body weight, a silk ligature was placed around their maxillary right second molar in order to induce bone loss. The non-ligated left side served as a control. Sixty days later, these animals were sacrificed by anaesthetic overdose. After routine laboratorial processing, images of the histological sections were digitized and submitted for histometric measurement using two parameters: histological attachment loss and bone loss.Results: on the ligated side, G1 presented with greater histological attachment and bone loss than G2 (p < 0.05). on the non-ligated control side, neither of the groups presented with alterations in these parameters (p > 0.05).Conclusion: The chronic stress regimen imposed on pregnant rats produced a greater progression of ligature-induced bone loss in their adult offspring. (C) 0 2011 Elsevier Ltd. All rights reserved.
Keywords: Behavioural research; Alveolar bone loss; Rats; Inbred Lew